Literature Review: Teacher Strategies in Civics Learning in Elementary Schools to Increase Students' Learning Motivation Students - Sukma, Nadhifah Bayu; Septiana Ardiningsih; Azizah , Ulfa Aliyatul; Rawanoko, Endrise Septina (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2024)
Citizenship Education (PKN) in Elementary Schools (SD) has an important role in shaping the character and social skills of students. However, one of the challenges faced is how to increase students' learning motivation in participating in PKN learning. Monotonous learning and material that tends to be abstract often make students less interested. Therefore, this research aims to analyze various strategies that can be implemented by teachers in PKN learning to increase student learning motivation. This research uses the Systematic Literature Review (SLR) method. Based on a review of literature from various studies, several effective strategies were found, such as the use of ice breaking techniques, counseling guidance, story and game methods, as well as the application of technology in learning. The use of approaches that are varied and relevant to students' lives has been proven to be able to increase their involvement in the learning process. Thus, teachers are expected to be able to implement innovative and fun strategies to motivate students in PKN learning, so that learning objectives can be achieved optimally.